Pembelajaran Akidah Akhlak Dimasa Pandemi - Daryani Umbara; Enoh; Ikin Asikin (Bandung Conference Series: Islamic Education, 2022)
Abstract. The objectives of this study are to: (1) describe the learning planning of moral aqidah education at MI Babur Royyan during a pandemic. (2) Describing the implementation of moral aqidah education learning at MI Babur Royyan during a pandemic. (3) Describe the evaluation of moral aqidah education at MI Babur Royyan during a pandemic. (4) Describe the supporting and inhibiting factors of moral aqidah education at MI Babur Royyan during the pandemic. This research uses a qualitative approach and the type is descriptive qualitative. The research is located at MI Babur Royyan. In-depth interviews were conducted with MI school principal Babur Royyan, Akhlah Akidah teachers, and several sixth grade students accompanied by documentation and observations made by researchers in collecting research data. The results of this study indicate that: (1) learning planning at MI Babur Royan During this pandemic, it is still following the recommendations of the government and madrasa policies in planning learning during the pandemic. (2) The implementation of moral aqidah learning at MI Babur Royan is carried out online and offline. Online learning is carried out through Whats APP groups and offline learning is carried out with a limited time, the learning process uses the lecture method, question and answer. (3) the evaluation/assessment of Akidah Akhlak Education is carried out by assessing skills through daily assignments given through whats app groups, Attitude assessment is carried out through teacher observations during offline learning, and knowledge assessment is carried out through exams conducted offline by taking questions at school and do it at home. (3) the supporting factor for learning morals during this pandemic is cellphones owned by students, while the constraining factor is the power of the internet, besides that teachers find it difficult to controlcellphones in using cellphones. Abstrak. Adapun tujuan penelitian ini adalah untuk: (1)mendeskripsikan perencanaan pembelajaran Pendidikan akidah akhlak di MI Babur Royyan pada pandemic. (2)Mendeskripsikan pelaksanaan pembelajaran Pendidikan akidah akhlak di MI Babur Royyan pada pandemic. (3)Mendeskripsikan evaluasi Pendidikan akidah akhlak Di MI Babur Royyan Pada pandemic. (4)Mendeskripsikan factor pendukung dan penghambat Pendidikan akidah akhlak Di MI Babur Royyan Pada pandemic. Penelitian ini menggunakan pendekatan kualitatif dan jenisnya berupa deskriptif kualitatif. Penelitian berlokasi di MI Babur Royyan. Wawancara mendalam dilakukan Bersama kepala sekolah MI Babur Royyan, Guru akidah akhlah, dan beberapa siswa kelas VI disertai dengan dokumentasi dan observasi yang dilakukan peneliti dalam mengambil data penelitian. Hasil penelitian ini menunjukan bahwa: (1) perencanaan pembelajaran di MI Babur Royan Pada masa pandemic ini tetap mengikuti anjuran pemerinta dan kebijakan madrasah dalam perencanaan pembelajaran dimasa pandemic. (2) Pelaksanaan pembelajaran akidah akhlak di MI Babur Royan dilakukan dengan daring dan luring. Pembelajaran daring dilakukan melaului Whats APP grup dan pembelajaran luring dilaksanakan dengan waktu terbatas, proses pembelajaranya menggunakan metode ceramah, tanya jawab. (3) evaluasi/penilaian Pendidkan Akidah Akhlak dilakukan dengan penilaian keterampilan lewat tugas tugas harian yang diberikan melalui whats app grup, penilaian Sikap dilakukan melalui observasi guru pada saat pembelajaran luring, dan penilaian pengetahuan dilakukan melalui ujian yang dilakukan secara luring dengan mengambil soal disekolah dan mengerjakanya dirumah. (3) factor pendukung pembelajaran akidah akhlak dimasa pandemic ini yaitu hanphone yang dimiliki siswa, sedangkan factor penghamat yaitu kekuatan internet, selain itu juga guru sulit mengontrol penggunaan hanphone siswa dalam penggunaan hanphone.